The Role of IL-4 Receptor Alpha signalling on Foxp3 T Regulatory cells in Listeriosis and Tuberculosis - Chia, Julius Ebua (Division of Immunology, 2021)
T regulatory cells are critical in the maintenance of self-tolerance, immune homeostasis and regulation of the immune system. Cytokine signalling is a dominant component of environmental signals which controls the function of Forkhead box P3 (Foxp3) regulatory T cells. This thesis addressed the hypothesis that interleukin-4 receptor alpha (IL-4Rα) signalling on T regulatory cells (T reg) play a role in the stability of T reg cells. Loss of IL-4Rα signalling on T reg cells may shift the immune balance from a Foxp3+ T reg to a Th1 effector function essential for Th1 disease outcome. Regulatory cells have a major function to dampen cytokine production; however, this role can be detrimental for host-protective immune responses in diseases such as tuberculosis. Here, we used two Th1 models of intracellular pathogens Listeria monocytogenes (Lm) and Mycobacterium tuberculosis (Mtb), to understand the role of IL-4Rα signalling on Foxp3+ T regulatory cells. Infection studies with L. monocytogenes demonstrated an impairment of T reg responses, with a decreased bacterial burden and diminished pathology both in the liver and spleen at 7 days post-infection, ultimately translated in better survival. Mechanistically, enhanced Th1 signature with the characteristic T-bet transcriptional factor and increased effector T cells producing IFN-γ, IL-2 following ex-vivo stimulation with PMA/Ionomycin, and heat-killed Lm (HKLM) were observed in Foxp3creIL-4Rα-/lox mice. Furthermore, CD8+ T cells of Foxp3creIL-4Rα-/lox mice showed increased cytotoxicity (Granzyme-B secretion) with higher proliferation capacity (Ki-67), better survival (Bcl-2) and decreased apoptosis (activated caspase3), suggesting contribution towards the observed protection against listeriosis. Subsequently, we investigated the role of IL-4Rα on Foxp3 T reg cells in Mycobacterium tuberculosis infection. To our surprise, in contrast to Lm infection, survival Survival of Mtb-infected Foxp3creIL-4Rα-/lox mice was similar to littermate control following infection with an intermediate dose of Mtb (H37Rv). We observed no differences in acute and chronic stages of infection in bacterial burden and histopathological scores in Foxp3creIL-4Rα-/lox mice when compared to littermate control animals in acute and chronic stages of infection. Importantly, Mtb infected FoxP3creIL-4Rα-/lox mice, exhibited significantly enhanced CD4+ T effector functions with increased pro-inflammatory cytokine secretion upon stimulation ex-vivo.